Neuro-immune crosstalk in depressive symptoms of multiple sclerosis - Wang, Chao; Zhou, Yulin; Feinstein, Anthony (Neurobiology of disease, 2023)
Depressive disorders can occur in up to 50% of people with multiple sclerosis in their lifetime. If left untreated, comorbid major depressive disorders may not spontaneously remit and is associated with an increased morbidity and mortality. Conversely, epidemiological evidence supports increased psychiatric visit as a significant prodromal event prior to diagnosis of MS. Are there common molecular pathways that contribute to the co-development of MS and psychiatric illnesses? We discuss immune cells that are dysregulated in MS and how such dysregulation can induce or protect against depressive symptoms. This is not meant to be a comprehensive review of all molecular pathways but rather a framework to guide future investigations of immune responses in depressed versus euthymic people with MS. Currently, there is weak evidence supporting the use of antidepressant medication in comorbid MS patients. It is our hope that by better understanding the neuroimmune crosstalk in the context of depression in MS, we can enhance the potential for future therapeutic options. •People with MS are 2–3 times more likely to develop MDD compared to the general popualtion.•Depression and MS share certain key immune system changes,•There is equivocal evidence supporting the effectiveness of antidepressant medication in MS-related depression.•Selected Disease Modifying Therapies may improve depression in people with MS.